Flexible microwave absorbers based on barium hexaferrite, carbon black, and nitrile rubber for 2-12 GHz applications - Vinayasree, S.; Soloman, M. A.; Sunny, Vijutha; Mohanan, P.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Applied Physics, 2014)
Flexile single layer electromagnetic wave absorbers were designed by incorporating appropriate amounts of carbon black in a nitrile butadiene rubber matrix along with an optimized amount of magnetic counterpart, namely, barium hexaferrite for applications in S, C, and X-bands. Effective dielectric permittivity and magnetic permeability were measured using cavity perturbation method in the frequency range of 2-12 GHz. The microwave absorbing characteristics of the composites were studied in the S, C, and X-bands employing a model in which an electromagnetic wave is incident normally on a metal terminated single layer. Reflection loss exceeding -20 dB is obtained for all the samples in a wide frequency range of 2-12 GHz when an appropriate absorber thickness between 5 and 9 mm is chosen. The impact of carbon black is clearly observed in the optimized composites on the mechanical strength, thickness, band width of absorption, dielectric properties, and absorptivity. (C) 2014 AIP Publishing LLC.

Magnetically tunable liquid dielectric with giant dielectric permittivity based on core-shell superparamagnetic iron oxide - Vinayasree, S.; Nitha, T. S.; Tiwary, C. S.; Ajayan, P. M.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2018)
A liquid dielectric based on a core-shell architecture having a superparamagnetic iron oxide core and a shell of silicon dioxide was synthesized. The frequency dependence of dielectric properties was evaluated for different concentrations of iron oxide. The dependence of magnetic field on the dielectric properties was also studied. Aqueous ferrofluid exhibited a giant dielectric constant of 6.4 x 10(5) at 0.1 MHz at a concentration of 0.2 vol% and the loss tangent was 3. The large rise in dielectric constant at room temperature is modelled and explained using percolation theory and Maxwell-Wagner-Sillars type polarization. The ferrofluid is presumed to consist of nanocapacitor networks which are wired in series along the lateral direction and parallel along longitudinal direction. On the application of an external magnetic field, the chain formation and its alignment results in the variation of dielectric permittivity.

Stealth emulsion based on natural rubber latex, core-shell ferrofluid/carbon black in the S and X bands - Vinayasree, S.; Nair, Ajalesh Balachandran; Mani, Manoj; Archana, V. N.; Joseph, Rani; Mohanan, P.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2019)
A lossy dielectric with an appropriate magnetic property is one of the requirements of a stealth material. The thickness of the absorber and the corresponding bandwidth of absorption are also other deciding factors that determine the choice of the material as microwave absorbers. A stable emulsion, which is lossy as well as magnetic, is promising, since it can be coated on surfaces with required thickness in the desired band. A magnetic nanofluidic emulsion serves the purpose. A microwave absorbing emulsion based on natural rubber latex with core-shell magnetic nanoparticles, based on superparamagnetic iron oxide nanoparticles (SPIONs), was developed. The effect of additives like carbon black on the bandwidth of absorption was also studied as a function of weight percentage of carbon black. The complex dielectric permittivity and magnetic permeability were evaluated using a vector network analyser in the S and X bands. Furthermore, these results were modelled using surface impedance equations. These investigations revealed that the incorporation of carbon black enhances the bandwidth of absorption and an emulsion with the required dielectric permittivity and magnetic permeability can be tailored for stealth applications.
Keywords: carbon black; core-shell nanoparticles; ferrofluid; microwave absorbing paint; natural rubber latex